2重根号の逆数の総和

2重根号の逆数の総和
\(n\in\mathbb{N}\)とする。
以下が成り立つ。
\[ \sum_{k=1}^{n}\frac{1}{\sqrt{k+\sqrt{k^{2}-1}}}=\frac{\sqrt{2}}{2}\left(\sqrt{n+1}+\sqrt{n}-1\right) \]

\begin{align*} \sum_{k=1}^{n}\frac{1}{\sqrt{k+\sqrt{k^{2}-1}}} & =\sum_{k=1}^{n}\frac{1}{\sqrt{\frac{k+1}{2}}+\sqrt{\frac{k-1}{2}}}\\ & =\sqrt{2}\sum_{k=1}^{n}\frac{1}{\sqrt{k+1}+\sqrt{k-1}}\\ & =\frac{\sqrt{2}}{2}\sum_{k=1}^{n}\left(\sqrt{k+1}-\sqrt{k-1}\right)\\ & =\frac{\sqrt{2}}{2}\left(\sum_{k=2}^{n+1}\sqrt{k}-\sum_{k=0}^{n-1}\sqrt{k}\right)\\ & =\frac{\sqrt{2}}{2}\left(\sqrt{n+1}+\sqrt{n}-1\right) \end{align*}

ページ情報

タイトル

2重根号の逆数の総和

URL

https://www.nomuramath.com/yeht2xfq/

SNSボタン